2021
DOI: 10.3390/en14061571
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Critical Infrastructure Systems: A Systematic Literature Review

Abstract: Risk management is a fundamental approach to improving critical infrastructure systems’ safety against disruptive events. This approach focuses on designing robust critical infrastructure systems (CISs) that could resist disruptive events by minimizing the possible events’ probability and consequences using preventive and protective programs. However, recent disasters like COVID-19 have shown that most CISs cannot stand against all potential disruptions. Recently there is a transition from robust design to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 219 publications
(283 reference statements)
0
25
0
Order By: Relevance
“…Therefore, recently, systems managers have moved their attention from building a robust system by risk management to establish a resilient system using resilience management (Barabadi et al 2020). Robust systems experience sudden failure in case of disruption and lose their core value, while resilient systems absorb the adverse impacts, adapt to and recover their desired performance level after a disruption (Mottahedi et al 2021). The concept of resilience has spread from ecological systems into other domains (Holling 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recently, systems managers have moved their attention from building a robust system by risk management to establish a resilient system using resilience management (Barabadi et al 2020). Robust systems experience sudden failure in case of disruption and lose their core value, while resilient systems absorb the adverse impacts, adapt to and recover their desired performance level after a disruption (Mottahedi et al 2021). The concept of resilience has spread from ecological systems into other domains (Holling 1973).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Twumasi-Boakye and Sobanjo [51] reviewed the concept of resilience and its applications in various domains, with special emphasis in transport infrastructure. Mot-tahedi et al [52] conducted a systematic review, presented definitions of resilience in the discipline of CIs, identified 20 factors contributing to CIs resilience, and grouped and discussed resilience analysis approaches. Hosseini et al [53] summarized several definitions of resilience in different domains and focused on qualitative and quantitative assessment approaches and their subcategories.…”
Section: Introductionmentioning
confidence: 99%
“…The risk management model focuses on the design of robust critical infrastructure, and minimizes the probability of risk events and their consequences through a series of preventive and protective measures. However, most critical infrastructures cannot withstand all potential disruptive events (Mottahedi et al 2021). On September 25, 2015, 17 Sustainable Development Goals (SDGs) were formally adopted at the 70th United Nations Sustainable Development Summit.…”
Section: Introductionmentioning
confidence: 99%